Systemic treatment of advanced colorectal cancer with particular emphasis on the treatment methods reimbursed in Poland. - Marta Szumilak (Polish Pharmaceutical Society, 2022)
Colorectal cancer is a leading cause of cancer deaths worldwide. The number of patients diagnosed with the disease continues to increase. Approximately 20% of patients are diagnosed with metastatic disease, while in 35% of patients, metastatic relapse occurs after the treatment for earlier-stage colon cancer. Advances in molecular profiling of metastatic colorectal cancer and the development of molecularly targeted therapies have led to the individualization of diagnostic and therapeutic procedures. The treatment algorithm is tailored according to patient characteristics, tumour staging as well as factors initiating the tumour development, causing its progression, and determining its sensitivity or resistance to antitumour agents e.g. RAS/BRAF status or microsatellite instability. The primary treatment for advanced colorectal cancer is systematic therapy based on cytotoxic drugs e.g. fluoropyrimidines, oxaliplatin and irinotecan in various chemotherapy regimens as well as targeted therapy such as antibodies targeted to cellular growth factors (EGFR, VEGF), and their combinations. The efficacy of immune checkpoint inhibitors has been demonstrated as well. In Poland, the drug program entitled "The treatment of advanced colorectal cancer." is a special reimbursing framework ensuring patients access to expensive, modern, targeted therapy such as monoclonal antibodies against EGFR and VEGF or new antimetabolite trifluridine/tipiracil. The paper discusses the principles of sequential treatment of advanced colorectal cancer, with the emphasis on limitations in the access to individual drugs included in the recommendations in the context of the eligibility criteria for treatment in the drug program. Selected multi-drug chemotherapy regimens used in advanced colorectal cancer are presented, and special attention is paid to the aspect of patient safety in the treatment process and methods of reducing drug-related complications. Due to the significant evolution of the therapeutic landscape for the metastatic disease over the past years, the latest therapies offering hope for patients suffering from cancer with characteristic molecular features were also presented.